PELATIHAN PEMULIAAN TANAMAN MUCUNA BRACTEATA DI SMK NEGERI 2 RANTAU UTARA KABUPATEN LABUHANBATU - Siti Hartati Yusida Saragih; Kamsia Dorliana Sitanggang; Fauziah Hanum; Sahat Partahi Halomoan Tampubolon; Saiputra Saiputra (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Mucuna bracteata plant breeding training aims to improve students knowledge and skills in vegetative and generative plant propagation. Plant breeding is a combination of art, science and technology in assembling the genetic diversity of a particular plant population to be better or superior than before. Community service activities were carried out on Thursday, May 15, 2025 using socialization and training methods. This activity involved the active participation of participants in all stages of the process. This training covers the topic of vegetative and generative plant propagation. The training showed positive results where participants were able to understand how to select cuttings and prepare mucuna seeds and plant the cuttings and mucuna seeds in the planting medium. Keywords: mucuna, plant breeding, plant propagation